BIOLOGY OF WINDOWPANE OYSTER PLACENTA PLACENTA (LINNAEUS) IN KAKINADA BAY - Narasimham, K A (Indian Journal of Fisheries, 2011)
The windowpane oyster, Placenta placenta, attains an average length of122 mm in 1 year and 157 mm in 2 years. Spawning is biannual, in February-April and October-December, with minor variations. The oyster may spawn morethan once during the same spawning season. Majority of the oysters mature forthe first time at 53 mm length. The condition index (% meat wt. in total wt.)varies from 8.7 to 18.7 and is higher prior to or at the beginning of spawningand declines with the completion of spawning. The condition index is slightlylower in the oysters infested by pea crab Pinnotheres placunae.